Estimation of Duration Gap and its Determinants for Islamic Banks: Empirical Evidence using Two-Step Robust GMM - Chattha, Jamshaid Anwar; Alhabshi, Syed Musa (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. Banking industry is risk management business. One specific risk is the rate of return risk (ROR) in the banking book. This study estimates the duration gap of IBs and its determinants in the context of ROR risk. Using Duration Gap Model and Two-Step Robust Generalized Method of Moments (GMM), with a sample of 50 IBs from 13 countries, for the period 2007-2015, our empirical findings are: (a) time series and cross-sectional duration gap of IBs reflecting significant variations across the banks and countries; (b) IBs have a general tendency of maintaining a higher duration gap compared to their conventional counterparts, and are exposed to increasing ROR risk due to their larger duration gaps and severe liquidity mismatches; and (c) there is significant difference in the estimated coefficients of idiosyncratic factors influencing the duration gaps of IBs. This study provides direction to the IBs to reflect upon the significance of liquidity mismatch risk.Abstrak. Industri perbankan adalah bisnis manajemen risiko. Salah satu risiko spesifik adalah risiko tingkat pengembalian (ROR) dalam banking book. Studi ini memperkirakan kesenjangan durasi IB dan determinannya dalam konteks risiko ROR. Menggunakan Duration Gap Model dan Two-Step Robust Generalized Method of Moments (GMM), dengan sampel 50 IB dari 13 negara, untuk periode 2007-2015, temuan empiris kami adalah: (a) time series dan cross-sectional durasi gap IB yang mencerminkan variasi signifikan di seluruh bank dan negara; (b) IB memiliki kecenderungan umum untuk mempertahankan kesenjangan durasi yang lebih tinggi dibandingkan dengan rekanan konvensional mereka, dan terpapar pada peningkatan risiko ROR karena kesenjangan durasi yang lebih besar dan ketidaksesuaian likuiditas yang parah; dan (c) terdapat perbedaan yang signifikan dalam estimasi koefisien faktor idiosinkratik yang mempengaruhi kesenjangan durasi IB. Studi ini memberikan arahan kepada IB untuk merenungkan pentingnya risiko ketidaksesuaian likuiditas.